Development and characterisation of gum arabic-kappa carrageenan composite film For hard capsule application - Jurida, Jamaludin (2021)
More than 50% of the hard capsule is manufactured from the animal gelatin, which may risk animal disease and religious prohibited source of gelatin. This awareness of gelatin source has driven many new alternative plant-based hard capsule developments. The present study's objective is to formulate and produce potential hard capsule from mixtures of gum arabic and semi refined kappa carrageenan. The GA-SRC composites were prepared at different SRC weight ratios of 33% (GC33), 50% (GC50) and 67% (GC67). Polyethylene glycol (PEG 400) and alginate have been added at constant concentration. The control films of gum arabic film (GAF) and semi refined kappa carrageenan film (SRCF) have been compared to the composites. Samples properties were characterised for its mechanical properties, surface morphologies, thermal properties and disintegration time. The raw material elemental and functional characterisation of GA and SRC suggested a compatibility to form composites through hydrogen bonding formation. GAF demonstrated brittle property and has smooth surface morphology with some cracks. SCRF exhibited shrinkage and has a rough surface morphology with the tensile strength of around 25.51 MPa. The increment of SRC in composite films has increased the composite solution viscosity, tensile strength and capsule loop. The hard capsule formed from sample GC67 shows the highest tensile strength and capsule loop of 36.21 MPa and 34.11 N respectively at 1058 mPa.s solution viscosity. It was determined that the hard capsule disintegrated at 7.30 minutes. The addition of gum arabic was able to make the hard capsule film surface smoother. Thus, GC67 is potential for the development of hard capsule, and the objective of this research was achieved.